LOGISTICS INTEGRATION INFORMATION SYSTEM ENABLERS INFLUENCE ON OPERATIONS EFFICIENCY THROUGH SUPPLY CHAIN RISK MANAGEMENT: THE MODERATING ROLE OF SUPPLY CHAIN COMPLEXITY - Mohammed A. Al Doghan; Sanjar Mirzaliev (Operational Research in Engineering Sciences: Theory and Applications)
The study aimed to analyze the impact of information sharing, management information systems, and technology integration on operations logistics integration to improve operational efficiency. The study also tested the mediating effect of supply chain risk management and the moderating role of supply chain complexities in the context of Saudi Arabian manufacturing companies.  Cross-sectional quantitative data was collected from 320 manufacturing companies’ employees through self-administered questionnaires which were distributed through a convenient sampling technique. The SEM results show that information sharing, management information sharing, and technology integration positively and significantly impact operational logistics integration. Further operations logistics integration and supply chain risk management also positively and significantly impact on operational efficiency.  The indirect mediating effect showed that supply chain risk management was not significantly mediated between operations logistics integration and operational efficiency. In contrast, moderating effect results also show that supply chain complexity significantly strengthens the relationship between operations logistics integration and operational efficiency. These findings contributed that increasing, management information systems, information sharing, and technology integration is crucial for improving operational logistics integration. Besides, organizations should consider the role of supply chain complexity in strengthening the relationship between logistics integration and operational efficiency.